The multiplicative version of the edge Wiener index - Soltani, Abolghasem; Iranmanesh, Ali; Abdul Majid, Zanariah (University of Kragujevac, 2014)
The multiplicative Wiener index π, which was introduced by Ivan Gutman et al. in [5], is a molecular structure descriptor equal to the product of the distances between all pairs of vertices of the underlying molecular graph G. Also, Iranmanesh et al. in [7], introduced the edge-Wiener index of a graph. It obtains in term of the distances between all pairs of edges set of a graph. We define a new index called the multiplicative edge-Wiener index that is equal to product of distance between all pairs of edges set of a graph G. Moreover, we compute this index for some well- known graphs and we consider its relation to the edge-Wiener index in alkanes, as well.